2013
DOI: 10.1186/1471-2164-14-768
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of radiata pine branches reveals new insights into reaction wood formation with implications in plant gravitropism

Abstract: BackgroundFormation of compression (CW) and opposite wood (OW) in branches and bent trunks is an adaptive feature of conifer trees in response to various displacement forces, such as gravity, wind, snow and artificial bending. Several previous studies have characterized tracheids, wood and gene transcription in artificially or naturally bent conifer trunks. These studies have provided molecular basis of reaction wood formation in response to bending forces and gravity stimulus. However, little is known about r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 60 publications
(95 reference statements)
2
36
0
Order By: Relevance
“…Not surprisingly, large numbers of genes have been described as being differentially expressed in reaction wood vs normal wood in various angiosperm species, including Eucalyptus (Paux et al ., ), tulip tree ( L. tulipifera ) (Jin et al ., ), and poplar (Andersson‐Gunneras et al ., ; Chen et al ., ). In pines, large numbers of genes have been identified that are differentially expressed between compression wood and opposite wood, including cell division, cell wall, hormonal, and cytoskeleton‐related genes (Ramos et al ., ; Villalobos et al ., ; Li et al ., ), A crucial next step for gene expression studies is to describe how the thousands of genes involved in reaction wood development interact to affect changes in wood anatomy.…”
Section: Mechanisms Regulating Developmental Changes In Reaction Woodsmentioning
confidence: 99%
“…Not surprisingly, large numbers of genes have been described as being differentially expressed in reaction wood vs normal wood in various angiosperm species, including Eucalyptus (Paux et al ., ), tulip tree ( L. tulipifera ) (Jin et al ., ), and poplar (Andersson‐Gunneras et al ., ; Chen et al ., ). In pines, large numbers of genes have been identified that are differentially expressed between compression wood and opposite wood, including cell division, cell wall, hormonal, and cytoskeleton‐related genes (Ramos et al ., ; Villalobos et al ., ; Li et al ., ), A crucial next step for gene expression studies is to describe how the thousands of genes involved in reaction wood development interact to affect changes in wood anatomy.…”
Section: Mechanisms Regulating Developmental Changes In Reaction Woodsmentioning
confidence: 99%
“…The molecular machinery behind MFA determination is still unclear; however, many quantitative trait loci (QTL) have been identified for wood and fibre properties, including MFA [93][94][95], and some genes have been identified as candidates [95][96][97][98][99]. Reaction wood (RW) has proved to be a useful model system in attempts to better understand the molecular basis of wood formation [100] and several studies have published transcriptomes of angiosperm and gymnosperm RW [101][102][103]. A large number of genes were reported to be highly expressed in RW, among them some encoding arabinogalactan proteins (AGPs), fasciclin-like arabinogalactan proteins (FLAs) and α and β-tubulins [102,[104][105][106][107][108].…”
Section: Molecular Control Of Mfamentioning
confidence: 99%
“…Reaction wood (RW) has proved to be a useful model system in attempts to better understand the molecular basis of wood formation [100] and several studies have published transcriptomes of angiosperm and gymnosperm RW [101][102][103]. A large number of genes were reported to be highly expressed in RW, among them some encoding arabinogalactan proteins (AGPs), fasciclin-like arabinogalactan proteins (FLAs) and α and β-tubulins [102,[104][105][106][107][108].…”
Section: Molecular Control Of Mfamentioning
confidence: 99%
“…differential genes, transcripts or probes (%): The number in parentheses corresponds to the percentage (%) of differential genes (transcripts or probes) relative to the total number of analyzed genes (transcripts or probes). Li, Yang, & Wu, 2013;Ralph et al, 2006;Villalobos et al, 2012) and long-oligonucleotide microarrays (e.g. Hybridization methods used microarray which contains a collection of probes spotted or printed onto a glass surface.…”
Section: Large-scale Rna Transcript Profiling Methodsmentioning
confidence: 99%